Definition, prevalence, and clinical significance of mitral annular disjunction in different patient cohorts: A systematic review. Issue 3 (4th February 2022) - Bennett, Sadie; Tafuro, Jacopo; Duckett, Simon; Appaji, Anik; Khan, Jamal Nasir; Heatlie, Grant; Cubukcu, Arzu; Kwok, Chun Shing
Abstract: Background: Mitral annular disjunction (MAD) is a structural abnormality involving a distinct separation of the left atrium/mitral valve annulus and myocardium continuum. The literature around MAD has increased over recent years, thus we sought to review the current data on the definition, prevalence, and clinical outcomes of MAD. Methods: A search of MEDLINE and EMBASE was conducted to identify studies which evaluated MAD in any patient cohort. The study results were synthesized narratively. Results: A total of 12 studies were included with 3925 patients (average age 62 years, 63% male). The pooled prevalence of MAD in patients with mitral valve prolapse and/or Barlow's disease was 30.1%. In a general population, MAD prevalence was 8.7%. The definition of MAD was not consistent across all studies. In terms of clinical outcomes, only one study reported MAD to be associated with ventricular arrhythmias. Conclusions: MAD is an increasingly recognized finding amongst patients undergoing cardiac imaging. This review highlights the need for agreed definitions for clinically significant MAD and how identified MAD should be managed. At present, there is insufficient evidence that MAD is associated adverse clinical outcomes.